2019
DOI: 10.1007/s00520-019-05118-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring oncology nurses’ perception of the consequences of clinical empathy in patients and nurses: a qualitative study

Abstract: Purpose Clinical empathy is the ability to understand the patient's situation, perspective, feelings, and actions, based on the patient's perception, in a helping or therapeutic way. This study was conducted with the aim of exploring oncology nurses' perception of the consequences of clinical empathy in patients and nurses and the factors influencing it. Methods A qualitative study was conducted by semi-structured face-to-face interviews. The participants were 6 male and 9 female oncology nurses who were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…This nursing method has been widely applied in clinical practice with remarkable effects, but its application in patients undergoing tension-free inguinal herniorrhaphy remains insufficient [ 6 – 8 ]. Empathy nursing aims to express the understanding of patients' inner changes so that patients can enjoy private nursing services and improve confidence, which will promote the improvement of patients' lousy mood, enable patients to accept surgery with a good attitude, and further promote the smooth operation of the surgery [ 9 , 10 ]. In the present study, nursing based on a quantitative evaluation strategy combined with empathic nursing was applied to patients with tension-free inguinal herniorrhaphy and the nursing effect was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This nursing method has been widely applied in clinical practice with remarkable effects, but its application in patients undergoing tension-free inguinal herniorrhaphy remains insufficient [ 6 – 8 ]. Empathy nursing aims to express the understanding of patients' inner changes so that patients can enjoy private nursing services and improve confidence, which will promote the improvement of patients' lousy mood, enable patients to accept surgery with a good attitude, and further promote the smooth operation of the surgery [ 9 , 10 ]. In the present study, nursing based on a quantitative evaluation strategy combined with empathic nursing was applied to patients with tension-free inguinal herniorrhaphy and the nursing effect was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…15 On one hand, empathy increases the level of emotional well-being, resilience, and satisfaction in nurses, 30,31 and on the other hand, it facilitates wound healing and pain relief, and decreases the development of complications in chronic diseases and increases the survival rate of patients. 32,33 Fernandez and…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that empathy has many positive effects on nurses and patients 15 . On one hand, empathy increases the level of emotional well‐being, resilience, and satisfaction in nurses, 30,31 and on the other hand, it facilitates wound healing and pain relief, and decreases the development of complications in chronic diseases and increases the survival rate of patients 32,33 . Fernandez and Zahavi 12 point out that it is not simple to understand and respond compassionately to patients and empathize with them, especially in complex diseases, nurses face difficulty in expressing compassion.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is concept hard to understand, empathy is defined as a mirror in our brain enabling us to put ourselves in someone's shoes and the main objective is to be able to completely understand the opposite person (1). Clinic empathy is the ability of understanding the state, viewpoint, feelings and actions of the patient based on their perceptions in an auxiliary or therapeutic way (2). When a care is provided to the patients with this point of view, the performances of the health professionals increase and their chance of experiencing burnout decreases (3,4).…”
Section: Introductionmentioning
confidence: 99%